ISOLASI DAN IDENTIFIKASI KAFEIN DALAM EKSTRAK AIR DAUN BENALU TEH, SCURRULA JUNGHUNII, LORANTHACEAE - Risma Marisi Tambunan; Bustanussalam Bustanussalam; Partomuan Simanjuntak; Retno Murwani (JURNAL ILMU KEFARMASIAN INDONESIA, 2003)
A known compound caffeine from the water extract of parasitic tea plants, Scurrula junghunii (Loranthaceae) have been isolated and identified. Identification the compound based on spectra of ultraviolet, infra red, nuclear magnetic resonance ('H- & 13C-NMR) and mass spectra.